Umweltfor̈dermaßnahmen in der Landwirtschaft - Teilnehmerauswahl durch Ausschreibungen? - Karin Holm-Mul̈ler; Volker Radke; Jur̈gen Weis (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Agri-environmental Programs - Using Auctions to Select Participants?Agri-environmental programs offering uniform payments to farmers achieved only low participation ratios in some regions whereas, in other regions, windfall profits arose. Auctions leading to individual payments equal to farmers' bids could solve this problem. Simulations showing auctions' efficiency gains are based on critical assumptions though. In this article the validity of these assumptions is discussed for different auction designs and different subprograms. We find that extensification programs offer the best conditions for successful auctions. However, it seems counterproductive to use auctions for choosing among different areas in environmental contracting.
Keywords: 330; Agrarpolitik; Umweltpolitik; Agrarsubvention; Umweltschutz; Effizienz; Auktionstheorie; Deutschland